Knock Three Times! - Webb, Marion St John (Wordsworth Editions Ltd, 1994)
Molly is desperately disappointed when instead of the longed for silver bangle,her aunt phoebe sends her a small grey pumpkin shaped pincushion for her birthday.
Keywords: Juvenile literature-Brothers and sisters-Magic-Adventure-Fiction